2018
DOI: 10.1111/cts.12566
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic and Exposure–dizziness Modeling for a Metabotropic Glutamate Receptor Subtype 5 Negative Allosteric Modulator in Major Depressive Disorder Patients

Abstract: Dizziness, the most frequently observed adverse event in patients with major depressive disorder, was observed with basimglurant, a selective, orally active metabotropic glutamate receptor subtype 5 negative allosteric modulator. The potential relationship between dizziness and basimglurant exposure was explored. The pharmacokinetics of basimglurant was characterized with nonlinear mixed effects modeling using data from 288 trial participants enrolled in five clinical trials. The pharmacokinetics of basimglura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It participates in physiological processes such as the plastic changes of learning, memorizing, and synaptic transmission efficiency ( Francesconi et al, 2004 ). Studies have found that mGluR5mRNA is associated with schizophrenia ( Matosin et al, 2018 ), depression ( Cosson et al, 2018 ), autism ( D’Antoni et al, 2014 ), Parkinson’s ( Vallano et al, 2013 ), Alzheimer’s ( Zhang et al, 2019 ), and many other neurological diseases. There are three subtypes of NMDAR—NR1, NR2, and NR3—among which NR1 plays a more extensive role ( Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It participates in physiological processes such as the plastic changes of learning, memorizing, and synaptic transmission efficiency ( Francesconi et al, 2004 ). Studies have found that mGluR5mRNA is associated with schizophrenia ( Matosin et al, 2018 ), depression ( Cosson et al, 2018 ), autism ( D’Antoni et al, 2014 ), Parkinson’s ( Vallano et al, 2013 ), Alzheimer’s ( Zhang et al, 2019 ), and many other neurological diseases. There are three subtypes of NMDAR—NR1, NR2, and NR3—among which NR1 plays a more extensive role ( Zhao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was an unusually high placebo response rate in this trial. Pooled pharmacokinetic data from four phase I and one phase II studies also suggested that clearance was twofold higher in smokers and 40% higher in males [175]. Due to the negative results on the phase IIb study conducted, this drug has not been cleared by FDA to be used for refractory MDD.…”
Section: Metabotropic Glutamate Receptor Negative Modulationmentioning
confidence: 99%
“…As understanding exposure-mGlu 5 RO relationships is important in achieving the right level of mGlu 5 target engagement for positive efficacy in a therapeutic setting, we studied the plasma and brain exposure-RO relationships of dipraglurant, basimglurant, mavoglurant, and HTL0014242, a new mGlu 5 -selective NAM (Christopher et al, 2015). The comparative data for this analysis are derived from experimental data and supplemented by published mGlu 5 RO and exposure data across species (Bennett et al, 2014;Lindemann et al, 2015;Quiroz et al, 2016;Tison et al, 2016;Cosson et al, 2018). As this study will demonstrate, when accounting for mGlu 5 affinity and brain exposure, exposure-RO relationships were similar across species and different mGlu 5 NAMs and in agreement with the simple E max model.…”
Section: Introductionmentioning
confidence: 99%